Pinkalicious and the pink parakeet - Kann, Victoria (New York, NY Harper, an imprint of HarperCollinsPublishers, 2015)
When Pinkalicious goes on a class trip to the birdhouse, she can't wait to see all the different birds -- especially the rare pink parakeet! Pinkalicious sees lovebirds, peacocks, toucans, and even one very chatty parrot, but no parakeet -- until she spies it escaping from the birdhouse! Everyone gets in a flap, and it's up to Pinkalicious to bring her feathered friend back home
Guided reading level J
Ages 4-8
2 13
Keywords: Aviaries -- Juvenile fiction; Aviaries; Birds -- Juvenile fiction; Birds; Lost articles -- Juvenile fiction; Lost articles; School field trips -- Juvenile fiction; School field trips; Birds -- Fiction; Lost and found possessions -- Fiction; Pink -- Fiction; School field trips -- Fiction; Fiction; Juvenile works